Use of topical imiquimod in the treatment of VIN: a case report and review of the literature - Chelsea Grimes, BS, MS; Cheri Cunningham, BS; Michael Lee, MD; Andrea Murina, MD (Wolters Kluwer, 2016)
Vulvar intraepithelial neoplasia (VIN) is a premalignant disease of the vulvar squamous epithelium. Standard treatment for VIN lesions is surgical excision. Alternative therapeutic options for conservative treatment have been sought by patients to prevent disfigurement and to preserve sexual function. We present such a patient in whom topical imiquimod was used with a successful outcome. Imiquimod is effective in the treatment of VIN, as well as convenient, self-administered, and generally well tolerated. Keywords: vulvar intraepithelial neoplasia, Bowen's disease, squamous cell carcinoma in situ, imiquimod